Numerical and experimental studies of coherent Smith-Purcell radiation - Bakkali Taheri, F (2016)
This thesis investigates the properties of coherent Smith-Purcell radiation (cSPr) at femtosecond-scale in the case of electrons bunches in the ultrarelativistic regimes. Of particular interest is the use of cSPR as a diagnostic tool to determine the longitudinal time profiles of such bunches, the study of azimuthal distribution of the radiated energy, and a contribution to the understanding of polarization properties. The study consists in a first theoretical part carried mostly in the context of the surface-current theory, supported with insights from particle-in-cell simulations. Then, as a step toward a better determination of time profile, the question of phase reconstruction is addressed through the design of a new algorithm proposed in this thesis and tested in known challenging cases. Experimental results are then presented, spanning shifts having taken place at the FACET facility at SLAC, Stanford, between 2013 and 2015.